Pelatihan Publik Speaking dalam Meningkatkan Self Confident Murid di MTs SINOA - Akbar, Andi Muh.; Kasmawati, Andi; Jusman, Jusman (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: Public speaking training in increasing students' self-confidence at MTS Sinoa is an activity that is carried out with the aim of increasing students' self-confidence or self-confidence in speaking in public, through several activities and techniques, where students are expected to be able to convey their ideas or concepts clearly. clear, effective and confident. Methodology: The effectiveness of public speaking training in increasing self-confidence using the knowledge sharing research method with an FGD (focus group discussion) approach, which is designed specifically for students by combining communication theory and direct practice. Results: The results of this public speaking training that has been implemented can create significant changes. Conclusions: In the world of education, the learning process is very important and supports students' cognitive and numerical factors, one of which is good communication skills. Limitations: There are several limitations to public speaking training at MTS Sinoa, namely the limited time in the school curriculum which often makes public speaking training short in duration, as a result students may not have enough time to really master this skill thoroughly, furthermore regarding inadequate resources to carry it out. quality public speaking training Contribution: Therefore, the public speaking training that has been implemented has a positive correlation between increasing interest in learning and increasing academic aspects such as percentages and discussions between teachers and students, especially MTs Sinoa, so that it is able to encourage the SDGs program which has 17 global goals, one of which is point 4, namely the quality of education.